Deep venous thrombosis induced by intravenous thrombogenic drugs - Dr. Chito Singh Thokchom; Dr. Chinglensana Laitonjam; Dr. Sunilkumar Singh Salam; Dr. Yumnam Priyabarta Singh; Dr. Nongmaithem Mackson (International Journal of Medical Research and Review, 2020)
Background: Deep vein thrombosis (DVT) is a major preventable cause of morbidity and mortality worldwide with the potential to cause a dreaded pulmonary embolism (PE). Disease and patient-specific considerations are preferably incorporated into therapeutic options for effective management.Materials and methods: Sixty-eight cases of acute deep vein thrombosis were treated within a period of 3 years from January 2016. All the cases were subjected to routine investigations with the Doppler study of the affected limb. Low molecular weight heparin (dalteparin) was administered in all the cases for a period of 15 days and the Doppler study was repeated at the end of the drug therapy. After the course of low molecular weight heparin, the patients were given acenocoumarol 2mg daily. Estimation of partial thromboplastin time and prothrombin time were performed before starting and during the treatment of the low molecular weight heparin and acenocoumarol regularly. A venogram was done only when the repeated Doppler study revealed unsatisfactory response to low molecular weight heparin therapy. Eight cases underwent thrombectomy and the postoperative period was uneventful.Results: Age group of 21-30 years was most affected (80.8%) with right lower limb being the commonest affected site of injection and associated lesions.Conclusion: DVT in the young population remains a challenge to the evaluating clinician. A variety of disease states can alter the anticoagulant factors. Urgent diagnosis and appropriate intervention carry paramount importance.